Regulation of cell signaling pathways by Wogonin in different cancers: Mechanistic review - Butt, Ghazala; Ozbey, Ulku; Malik, Durr-e-shahwar; Attar, Rukset; Youssef, Lara; Farooqi, Ammad Ahmad (Cellular and Molecular Biology, 2021)
Natural products have historically been invaluable as a premium source of therapeutic agents. Recent advancements in genomics and structural biology have portrayed a high-resolution landscape of the diversity of proteins targeted by pharmacologically active products from natural sources. Natural product research has generated valuable wealth of information and cutting-edge research-works have leveraged our conceptual knowledge altogether to a new level. Wogonin (5,7-dihydroxy-8-methoxyflavone) is an O-methylated flavone and has attracted noteworthy appreciation because of its ability to pharmacologically target plethora of cell signaling pathways in different cancers. In this mini-review, we have gathered scattered pieces of available scientific evidence to summarize how wogonin pharmaceutically targeted Wnt/β-catenin, JAK/STAT, VEGF/VEGFR and TRAIL-driven apoptotic pathways in wide variety of cancers. We have also critically analyzed how wogonin prevented carcinogenesis and metastasis in tumor-bearing mice. Although researchers have uncovered pleiotropic role of wogonin in the regulation of different oncogenic signaling cascades but there are visible knowledge gaps in our understanding related to regulation of non-coding RNAs by wogonin. Future studies must converge on the unraveling of additional drug targets for wogonin to achieve a fuller and realistic understanding of the chemopreventive properties of wogonin.